Research progress in organic solar cells - Dong, Yu (Transactions on Environment, Energy and Earth Sciences, 2024)
In recent years, with the rapid development of human society, energy consumption has been increasing, and the use of traditional fossil fuels has also led to a certain amount of pollution. Solar energy, as a new type of energy, stands out due to its clean and large capacity, and solar cells have attracted hot attention. Although the overall development of solar cells started relatively late, the field of organic solar cells has benefited from breakthroughs in some materials and technologies, and has developed rapidly. This paper will introduce the basic principles of solar cells, summarize and analyze the development status of Schottky organic solar cells, donor acceptor materials, biomass based materials, and nanomaterials. It will summarize and analyze the efficiency improvement and performance optimization of these major categories of solar cells, draw prospects for future development in this field, and hope that organic solar cells will have more extensive applications in the future.